An Application of WQI and Correlation Matrix to Evaluate Groundwater Quality Around Brick Kilns of Loralai District Balochistan - Mohammad, Abida Dost; Rind, Rida Fatima (Journal of Asian Scientific Research, 2020)
The present study aimed to assess the quality of groundwater close to functional brick kilns of the Loralai district of Balochistan using the water quality index (WQI) Model. 15 samples were collected from the bore wells and tube wells situated near brick kilns. To appraise the WQI groundwater samples were subjected to an extensive analysis of physicochemical such as color, odor, taste, pH, Electrical conductivity (EC), Total dissolved solids (TDS), Total hardness (TH), Sulfate (SO4), Chloride (Cl), Fluoride (F), Sodium (Na), Potassium (K), & Arsenic (As). GIS was used to map the sampling location. The descriptive statistical approach and correlation matrix were successfully applied to study the variation and determining the interdependence of various parameters in the Loralai district of Balochistan. Based on the Water Quality Index (WQI) results in the majority of the value of the samples ranged from 48-204 falling in poor water quality category. The assessment proclaims that groundwater sources surrounding brick kilns need a reliable degree of treatment before the consumption of end-users and should be protected from contamination in the future.